2019
DOI: 10.1002/jbm4.10129
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Imminent Risk of Nonvertebral Fracture in Older, High‐Risk Women: The Framingham Osteoporosis Study

Abstract: Osteoporosis treatment decisions are often based solely on BMD or on 10‐year fracture risk; little is known about factors increasing imminent fracture risk. Understanding factors contributing to imminent risk of fracture is potentially useful for personalizing therapy, especially among those at high risk. Our aim was to identify predictors of nonvertebral fracture for 1‐ and 2‐year periods in women at high risk for fracture. The Framingham Osteoporosis Study cohort included 1470 women (contributing 2778 observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…Our models show that most of the predictors of imminent risk include characteristics that reflect health status, which is likely to change over time, particularly in older individuals. This is consistent with a growing body of literature suggesting that an individual's fracture risk is dynamic, in that it varies over time and may be dependent on the specific combinations of risk factors that are present [18,[23][24][25][26][27]. Given that health status changes and medical events (e.g., myocardial infarction, stroke, Alzheimer's diagnosis) that affect factors such as physical functioning occur more frequently with increasing age, annual assessments of fracture risk would likely help better identify those patients most at imminent risk of fracture and support improved management of fracture risk in these patients [18,23,27].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our models show that most of the predictors of imminent risk include characteristics that reflect health status, which is likely to change over time, particularly in older individuals. This is consistent with a growing body of literature suggesting that an individual's fracture risk is dynamic, in that it varies over time and may be dependent on the specific combinations of risk factors that are present [18,[23][24][25][26][27]. Given that health status changes and medical events (e.g., myocardial infarction, stroke, Alzheimer's diagnosis) that affect factors such as physical functioning occur more frequently with increasing age, annual assessments of fracture risk would likely help better identify those patients most at imminent risk of fracture and support improved management of fracture risk in these patients [18,23,27].…”
Section: Discussionsupporting
confidence: 86%
“…While there is no broadly accepted definition of imminent fracture risk, we chose to focus on factors predicting fracture in the next year to add to the literature on assessing risk over a shorter time frame, in contrast to the traditional longer-term fracture risk prediction framework. Our findings align well with the growing body of literature on imminent risk of fracture, including observational studies which have consistently identified low BMD, prior fractures, age, poor health status, previous falls, specific comorbidities that influence physical and cognitive functioning (both of which are risk factors for falls), as well as other fall-related risk factors, as key predictors of the imminent risk of fracture [18,[23][24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 83%
“…Thus, we may postulate that part of the association between grip strength and fracture goes through BMD. The same may be the case for physical limitations and low self-perceived health which both have shown to be associated with hip fractures [42]. Low BMI is a wellknown risk factor for hip fracture.…”
Section: Comparison With Existing Studiesmentioning
confidence: 85%
“…( 12 ) Across these and other studies, factors other than recent fracture that have been reported to increase imminent risk include comorbidities, glucocorticoid therapy, falls, greater age, and lower bone mineral density (BMD). ( 13–15 ) Collectively, these data provide a strong rationale for early intervention after incident fracture, particularly that which has occurred at the spine or hip. In such individuals, skeletal anabolic therapy should be strongly considered in view of the evidence for greater and more rapid reduction in fracture risk when compared with antiresorptive drugs.…”
Section: Imminent Risk and Fraxmentioning
confidence: 99%